Composition, rhetoric, and disciplinarity - Malenczyk, Rita, 1959-; Miller-Cochran, Susan K.; Wardle, Elizabeth (Elizabeth Ann); Yancey, Kathleen Blake, 1950- (Utah State University Press, 2018)
As a discipline, can rhetoric and composition continue its historical commitment to pedagogy without sacrificing equal attention to other areas, such as research and theory? In this book, contributors address disagreements about what it means to be called a discipline rather than a profession or a field. -- Provided by publisher.